Investigation of Velocity Distribution in Open Channel Flows Based on Conditional Average of Turbulent Structures. (29th May 2017) - Han, Yu; Yang, Shu-Qing; Sivakumar, Muttucumaru; Qiu, Liu-Chao
Abstract : We report the development of a new analytical model similar to the Reynolds-averaged Navier-Stokes equations to determine the distribution of streamwise velocity by considering the bursting phenomenon. It is found that, in two-dimensional (2D) flows, the underlying mechanism of the wake law in 2D uniform flow is actually a result of up/down events. A special experiment was conducted to examine the newly derived analytical model, and good agreement is achieved between the experimental data in the inner region and the model's prediction. The obtained experimental data were also used to examine the DML-Law (dip-modified-log-law), MLW-Law (modified-log-wake law), and CML-Law (Cole's wake law), and the agreement is not very satisfactory in the outer region.